STIMULATING THE MSME PERFORMANCE MONITORING SYSTEM THROUGH IMPROVING PERFORMANCE AND IMPLEMENTING CREATIVE ECONOMICS - Zulkarnaini; Zulfikar; Muhammad Arifai; Kheriah; Lakharis Inuzula; Julia Alfianti; Reynold Herwinsyah (CV. Radja Publika, 2024)
Micro, Small and Medium Enterprises (MSMEs) are a symbol of the strength of a region that must be developed. To support the development of MSMEs which continue to grow, various strategies are needed, especially how to encourage effective and efficient performance improvement. If these conditions can be implemented well, the development of MSMEs will facilitate the monitoring system for MSME performance by regional governments as an important part of improving regional performance, in this case the Department of Industry, Trade, Cooperatives and MSMEs. Apart from that, the consequences will have a direct impact on increasing regional economic value, especially on the growth of the creative economy which arises from the growth of MSMEs based on local wisdom, namely sharia-based. Therefore, it is very necessary to innovate policies by regional governments as an effort to accelerate regional economic development. This research is empirical research through a conclusive research design, namely by using data analysis using the Confirmatory Factor Analysis (CFA) method with the aim of seeing the advantages or strengths of each dimension of the MSME performance variables and the implementation of a sharia-based creative economy. The population that will be taken is all MSMEs in Lhokseumawe City based on data sources from the Department of Industry, Trade, Cooperatives and UMKM as the authority to supervise or monitor the performance of MSMEs. The sample determination method uses simple random sampling using the Isacc & Michael Table technique . The research results explain that the performance of MSMEs has the greatest contribution when compared to the implementation of a sharia-based creative economy in the Lhokseumawe City area. The results of the research prove that there is a need for regional government policy innovation, in this case the Department of Industry, Trade, Cooperatives and MSMEs, especially regarding monitoring and stimulating the performance of MSMEs through the existence of programs that encourage increasing the application of a creative economy based on local wisdom so that regions have advantages as a basis for implementing sharia Islam in Aceh Province.